Editors’ Word - Ejdus, Filip; Kovačević, Marko; Vujinović, Nikola (Journal of Regional Security, 2018)
We are proud to present the first issue of Volume No. 8. of the Journal of Regional Security. The previous “blue volume” was a transitional one, introducing many editorial, visual and organizational changes. As is usually the case with transitions, apart from creative potential they also generate a number of challenges and uncertainties. The “burgundy volume”, which marks the seventh year since the establishment of the Journal, will hopefully be characterized by consolidation in terms of both quality and dynamic of the publication. This issue of the Journal of Regional Security brings four articles to its readers.